Catechism of the Catholic Church in Science in 1800s in Spain reflected in Hugh Hudson’s Finding Altamira 2016 - Fithriana Chalimah (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2020)
This paper explains about the reflection of Catechism of the Catholic Church in Science in 1800s in Spain of Hugh Hudson’s Finding Altamira (2016). The researcher uses qualitative data to analyze the data. The procedure of collecting uses watching, reading, identifying, classifying and identifying. The method of analyzing data in this research use displaying, explaining and interpreting. The aim of this study is to find: the first is the relation between the pastor and the scientists in 1800s, and the second is Catechism of Catholic church represented in Hugh Hudson’s Finding Altamira 2016. In this study, the researcher uses sociology of literature approach and theory of modern science. Keywords: Catechism, Catholic, Church, Science, Spain.